2013
DOI: 10.21608/resoncol.2013.880
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine, Dexamethasone, and Cisplatin (GDP) versus Dexamethasone,Cytarabine, and Cisplatin (DHAP) as Salvage Chemotherapy for Patients With Relapsed or Refractory Diffuse Large B-cell Lymphoma (DLBCL)

Abstract: IntroductIonNon Hodgkin lymphomas (NHLs) are the most commonly occurring hematologic malignancies in the United States. They represent 4% to 5% of all new cancer cases. There is 65,540 men and women (35,380 men and 30,160 women) ARM I "cisplatin 75mg/m2 on day 1, dexamethasone 40 mg on days 1-4, and gemcitabine 1000mg/m2 on days 1 and 8, given every 21 days" and ARM II, Patients received "cisplatin 75mg/m2 IV over 24 hours on day 1, dexamethasone as in arm A, and cytarabine 2gm/m2 IV over 3 hours every 12 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Another study done by Ismaeil et al 10 found no significant difference between both regimens after 6 cycles of treatment. They included 62 patients with relapsed or refractory NHL and they observed an ORR of 67.6% in GDP and 65% in DHAP group.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Another study done by Ismaeil et al 10 found no significant difference between both regimens after 6 cycles of treatment. They included 62 patients with relapsed or refractory NHL and they observed an ORR of 67.6% in GDP and 65% in DHAP group.…”
Section: Discussionmentioning
confidence: 87%
“…This correlated with results of Crump et al 9 who found no significant difference between both groups regarding toxicity except for nausea and febrile neutropenia. However, Ismaiel et al 10 found significant difference between both groups in febrile neutropenia, infection and stomatitis.…”
Section: Discussionmentioning
confidence: 94%